Functional, textural and sensory properties of dry pasta supplemented with lyophilized tomato matrix or with durum wheat bran extracts produced by supercritical carbon dioxide or ultrasound. (15th December 2016) - Pasqualone, Antonella; Gambacorta, Giuseppe; Summo, Carmine; Caponio, Francesco; Di Miceli, Giuseppe; Flagella, Zina; Marrese, Pier Paolo; Piro, Gabriella; Perrotta, Carla; De Bellis, Luigi; Lenucci, Marcello Salvatore
Highlights: Bran extracts were produced by ultrasounds and supercritical CO2 . Lyophilized matrix was produced from high lycopene tomato. Pasta was added of bran aqueous extract, oleoresin, lyophilized tomato. Bran oleoresin increased pasta antioxidant activity. Bran oleoresin-added pasta was sensory judged similar to control. Abstract: A study was carried out to produce functional pasta by adding bran aqueous extract (BW) and bran oleoresin (BO) obtained using ultrasound and supercritical CO2, respectively, or a powdery lyophilized tomato matrix (LT). The bioactive compounds, hydrophilic and lipophilic antioxidant activity (HAA and LAA) in vitro, were evaluated. BW supplementation did not improve antioxidant activity, whilst LT pasta showed unconventional taste and odor. BO pasta had good levels of tocochromanols (2551 μg/100 g pasta f.w.) and carotenoids (40.2 μg/100 g pasta f.w.), and the highest HAA and LAA. The oleoresin altered starch swelling and gluten network, as evidenced by scanning electron microscopy, therefore BO pasta had structural characteristics poor compared with the control (4.8% vs. 3.2% cooking loss), although this difference did not affect significantly overall sensory judgment (74 vs. 79 for BO and control, respectively). BO supplementation was most effective for increasing antioxidant activity without jeopardizing pasta quality.